Distal Biceps Femoris Tendon Tear in an Active-Duty Soldier: A Case Report and Review of the Literature - Unangst, Alicia; Tamate, Trent; Bottoni, Craig R.; Zhou, Liang (The Journal of Knee Surgery, 2022)
Distal hamstring injuries and tendon ruptures are rarer than their proximal counterparts, and literature on the management of these injuries is limited. We present a case report of an active-duty soldier who sustained an intratendinous rupture isolated to the long head of the biceps femoris, as well as a summary of the available evidence on this subject matter. A combined end-to-end repair with partial tenodesis to the intact short head allowed the patient a near-full return to military duties at 5 months postoperatively. Surgery combined with diligent, supervised rehabilitation may be effective in returning patients with intratendinous distal biceps femoris tendon tears to athletic lifestyles.
Keywords: orthopaedic; sport; knee; tendon; repair; military